To the necessity of palliative care of municipal level in the conditions of the regional subordination of oncology service (on the example of Novokuznetsk, Kemerovo region) - V. V. Zakharenkov; I. V. Viblaya; D. C. Svyatova (Acta Biomedica Scientifica, 2013)
It is emphasized that according to the WHO cancer is one of the leading causes of death in the world. The dynamic evaluation of the primary incidence rate of malignant neoplasms among the inhabitants of Novokuznetsk, Kemerovo Region, Siberian federal district of Russian Federation is given. It is shown that in Novokuznetsk value of an indicator of primary cancer incidence grew from 333,9 cases by 100 thousand population in 2005 to 372,5 cases on 100 thousand population in 2009 (totally for 18,4 %) and exceeds values of similar indicators in Russian Federation and Siberian federal district for 5 %, and indicators in the Kemerovo Region for 12 %. The ratio of the indicators in Novokuznetsk to the data in other territories is presented. It suggests that among designated territorial units the highest incidence of malignant tumors registered in Novokuznetsk. The deficit of health system capacity for inpatient care to cancer patients in the terminal stage of the disease is marked. During the 7-year period of supervision (2005-2011) the availability of hospital beds for the population of the Kemerovo Region was 11 ± 2,5 % lower than in the whole in Siberian federal district. The emphasis is placed on the fact that the deficiency of health care system limits the ability to satisfy the need for hospitalization of patients with a terminal stage of an oncological disease. The need of improvement of approaches to optimization of health system is indicated. The causes of the problems of palliative care for oncological patients are designated, the main ones are: lack of staging of rendering the palliative help, lack of integration of work of health system on ensuring the palliative help, imperfection of information support, etc. The direction for solving the existing problems is shown. Scientific and methodical base in support of its development is determined. The expected results are marked. They are the following: obtaining of reliable indicators about a condition of cancer incidence, development and implementation of improved models of palliative care in conditions of regional subordination of oncological service of Novokuznetsk, improving satisfaction of cancer patients in a terminal stage of cancer.